Effectiveness of Digital Learning Media Using 3D Animation to Improve Elementary School Science Learning Outcomes : Literatur Review - Anisa Putri; Rohmani (RUKASI: Jurnal Ilmiah Perkembangan Pendidikan dan Pembelajaran, 2024)
Digital learning media with 3D animation has become a trend in education, especially to improve science learning outcomes in elementary schools. This research examines the effectiveness of digital learning media using 3D animation in improving elementary school science learning outcomes. The method used is a literature review over a period of 5 years (2019-2023). The results of this research obtained data from the scholar.com database with the keyword digital learning using 3D animation in science subjects totaling 1,470 articles and 6 articles that met the inclusion criteria for analysis. Digital learning media with 3D animation is an effective learning media for improving elementary school science learning outcomes.